MANAJEMEN RISIKO DI ERA COVID-19 TERHADAP PEREKONOMIAN DAN UMKM DI INDONESIA - Ma'rufah, Laila; Widyaningsih, Bekti (Izdihar: Jurnal Ekonomi Syariah, 2023)
The Covid-19 pandemic was able to change almost all patterns of community activity in the world. Everything that invites crowds or the involvement of many people must be avoided. So that it will cause a lot of risk impacts in all sectors of life including the economic sector in it. Risk is a result that is not good and can hinder a certain goal. So good risk management is really needed in a situation like this in order to be able to deal with all the risks that arise due to Covid-19. This study aims to determine Risk Management in the Covid-19 era in the economic field. This type of research is a type of library research. The conclusions from the results of this study indicate that Risk Management in the Covid-19 era is in the current economic sector with various impacts on the economy due to the Covid-19 pandemic, namely difficulties in finding jobs, difficulties in meeting daily needs, not even having an income in meeting the necessities of life and there are many more risks that occur from other economic sectors. As for what the government is doing to minimize this risk, namely by issuing several monetary and fiscal policies in the hope of being able to restore the economic situation of the State of Indonesia.   Keywords: Risk Management , Covid-19, Community Economy, UMKM,